Pyoderma Gangrenosum associated with Paroxysmal Nocturnal Haemoglobinuria - Moura Filho, Francisco Ronaldo (2017)
Pyoderma gangrenosum is a chronic neutrophilic dermatosis with no established etiology. It is often associated with systemic diseases such as inflammatory rheumatic diseases, inflammatory bowel diseases, malignant neoplasms and haematological diseases including nocturnal paroxysmal hemoglobinuria. It presents as ulcerated and painful skin lesions with rapid and progressive evolution, mainly in the lower limbs. Ulcerations may arise spontaneously or induced by trauma (pathergy phenomenon). The period between the onset of the lesions and the diagnosis is usually prolonged. The diagnosis is based on clinical data and confirmed after the exclusion of other causes of cutaneous ulcerations. We report a case of Pyoderma gangrenosum in the left upper limb with onset after a traumatic event in a patient with nocturnal paroxysmal hemoglobinuria.